The concept of circular water value and its role in the design and implementation of circular desalination projects. The case of coal mines in Poland - Xevgenos, D.; Tourkodimitri, K. Panteleaki; Mortou, M.; Mitko, K.; Sapoutzi, D.; Stroutza, D.; Turek, M.; van Loosdrecht, M.C.M. (Desalination, 2024)
Circular economy has become a popular subject, attracting attention from academics, practitioners, and policy-makers alike. However, despite the excitement surrounding it, the concept of circular economy has been criticized for being vague and having multiple interpretations from different fields. As a result, there is a lack of evidence and guidance for practitioners, making it difficult to put into practice. Our goal is to fill this gap by bridging the design and implementation of circular economy solutions in the water sector. Through an exploratory study of two case studies, we have shown the significance of what we call as “circular water value” in the context of coal mining. This value is strongly influenced by the chemistry, concentration levels and purity of these effluents. We compared the circular value of the two cases (ranging from 2.5 to 6 euros per cubic meter) to the cost of the novel treatment system, developed by the authors through the EU-funded project ZERO BRINE, to capture this value. This allowed us to evaluate the potential for circular economy implementation. We suggest that this circular transition can offer significant opportunities to coal mining regions in enabling a just transition implementation. This is a topic that is increasingly gaining interest among academic and practitioner communities, further triggered by the recently adopted Just Transition Mechanism. This mechanism secures targeted support of 55 billion euro for the period 2021–2027 for the most affected regions within Europe. The concept of “circular water value” introduced in this article can serve as a tool for exploring the creation of emerging circular value chains from coal mines, as well as for other wastewater treatment and resource recovery projects in general. •Introducing the new concept of "Circular Water Value" to assess resource recovery in circular water projects.•Application of the concept for the case of coal mine effluent treatment and resource recovery•Contribution to bridging the design implementation gap in the circular economy business modeling field•A basic chemistry based concept to mainstream the circular water economy knowledge beyond the wastewater treatment domain